2015
DOI: 10.1039/c5tc00102a
|View full text |Cite
|
Sign up to set email alerts
|

The Sb2O3 redox route to obtain copper nanoparticles in glasses with plasmonic properties

Abstract: Production of oxide glasses containing CuII, CuI and Cu0 nanoparticles by redox process during melting without subsequent thermal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…9 However, preparation of Cu nanocomposites is a challenging task since copper can acquire various oxidation states (Cu 2+ , Cu + , Cu 0 ), and the predominant stability is for the Cu 2+ ion, especially for syntheses carried out in air atmosphere. 10 Hence, inclusion of suitable reducing agents such as tin(II) oxide 11,12 or antimony(III) oxide 13,14 as part of the glass material has been proposed, aiming to control the oxidation states of copper.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, preparation of Cu nanocomposites is a challenging task since copper can acquire various oxidation states (Cu 2+ , Cu + , Cu 0 ), and the predominant stability is for the Cu 2+ ion, especially for syntheses carried out in air atmosphere. 10 Hence, inclusion of suitable reducing agents such as tin(II) oxide 11,12 or antimony(III) oxide 13,14 as part of the glass material has been proposed, aiming to control the oxidation states of copper.…”
Section: Introductionmentioning
confidence: 99%
“…The Raman spectrum in the range of 200−750 cm −1 is very broad and is dominated by the Sb 2 O 3 vibrational modes. 47 It has been recently reported that the vitreous antimony materials exhibit a complex Raman spectrum consisting of three broad bands located at 605, 465, and 408 cm −1 . 48 The 605 cm −1 band was assigned to the antisymmetric stretching vibrations of the Sb−O−Sb bridges.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…However, the direct production of MNPs inside the glasses in melt-quench approach is an arduous task due to oxidation processes occurring at elevated temperature while melting the precursors. Douglas et al [19] have recently demonstrated that choosing the thermal reducing agent in the glass composition produces a highly uniform and homogeneous distribution of MNPs inside the glasses. In addition to the considerable reports on NLO properties glasses doped with MNPs, recently, Rajaramakrishna et al [20] have reported that gold NP-doped borate glasses demonstrated good saturable absorption (SA) at 532 nm, nanosecond (ns) pulses.…”
Section: Introductionmentioning
confidence: 99%